2010
DOI: 10.2337/dc10-0261
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Risk for Diabetes Incidence and Mortality in Korean Men and Women

Abstract: OBJECTIVEMounting evidence suggests that smoking is a cause of type 2 diabetes. We explored the association of cigarette smoking with diabetes incidence and mortality in a large cohort of Koreans.RESEARCH DESIGN AND METHODSA 14-year prospective cohort study was performed on 1,236,443 Korean men and women, aged 30–95 years at baseline, who underwent standardized biennial medical examinations provided by the National Health Insurance Corporation (NHIC). Incident diabetes was identified on the basis of outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 19 publications
7
71
2
1
Order By: Relevance
“…We defined smoking intensity as number of cigarettes smoked per day. We defined high‐intensity smoking as smoking more than 20 cigarettes daily based on previous published literature 16. We measured cumulative dose of smoking in “pack‐years,” which we calculated by multiplying the number of packs of cigarettes per day by the number of years smoking.…”
Section: Methodsmentioning
confidence: 99%
“…We defined smoking intensity as number of cigarettes smoked per day. We defined high‐intensity smoking as smoking more than 20 cigarettes daily based on previous published literature 16. We measured cumulative dose of smoking in “pack‐years,” which we calculated by multiplying the number of packs of cigarettes per day by the number of years smoking.…”
Section: Methodsmentioning
confidence: 99%
“…Given the recommendation that only a simple inverse variance weight be used when deriving the summary estimate, asymmetry was likely the product of a large Korean study, which provided 65% of participant data and reported a lower degree of risk reduction than most other studies (40). The impact of the Korean study upon modeled doseresponse curves was diminished after the addition of a random-effects weighting component in the primary analyses undertaken for this article (Supplementary Fig.…”
Section: Small-study Effectsmentioning
confidence: 99%
“…In the updated meta-analysis, the association between smoking and incident type 2 diabetes was slightly stronger for men (2). Two other studies, which were published after the cutoff date of the updated meta-analysis, also showed a slightly higher risk for men (16,17).…”
Section: Differences Between Men and Womenmentioning
confidence: 99%